Safety evaluation of the food enzyme α‐amylase from the genetically modified Bacillus amyloliquefaciens strain DP‐Czb53 - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Vittorio Silano; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Claude Lambré; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; et al. (EFSA Journal, 2020)
Abstract The food enzyme α‐amylase (4‐α‐d‐glucan glucohydrolase; EC 3.2.1.1) is produced with the genetically modified B. amyloliquefaciens strain DP‐Czb53 by Danisco US Inc. The genetic modifications do not raise safety concerns, except for the presence of a multicopy plasmid carrying known antimicrobial resistance genes. However, based on the absence of viable cells and DNA from the production organism in the food enzyme, this is not considered to be a risk. The food enzyme is intended to be used in starch processing for the production of glucose syrups. Toxicological studies and dietary exposure estimation were not considered necessary. Similarity of the amino acid sequence to those of known allergens was searched and one match was found. The Panel considered that, under the intended conditions of use, the risk of allergic sensitisation and elicitation reactions by dietary exposure cannot be excluded, but the likelihood for this to occur is considered to be low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns under the intended conditions of use.